Discovery Learning-Based E-Comic Media for Mathematics Subjects on Fractions in Grade IV Elementary School - Luh Deary Keistal Dewi; I Wayan Wiarta; Ni Luh Putu Agetania (Mimbar Pendidikan Indonesia, 2025)
Students’ understanding of fraction concepts in Grade IV mathematics remains relatively low. This is due to the abstract nature of the material and the lack of engaging and contextual learning media. This study aims to develop and examine the effectiveness of e-comic media based on the Discovery Learning model in enhancing students’ conceptual understanding of fractions. This is a development research employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study consisted of 22 fourth-grade students. Data were collected through observation, interviews, questionnaires, and tests. Instruments included observation sheets, interview guides, student response questionnaires, and conceptual understanding tests. Data analysis used a one-sample t-test. The results showed that the tvalue was 1.722, which is greater than the ttable value of 1.721 at a 5% significance level (df = 21), indicating that H0 is rejected and H1 is accepted. These findings demonstrate that the use of e-comic media based on Discovery Learning is effective in improving students’ understanding of fractions. It can be concluded that e-comics serve as an innovative and enjoyable learning alternative. The implication is that this media has the potential to be widely adopted in elementary mathematics instruction to foster active participation and enhance students’ conceptual understanding.